Human Pro-Social Motivation and the Maintenance of Social Order - Simon Gaechter (Center for Economic Studies and ifo Institute (CESifo), 2014)
This chapter presents some insights from basic behavioural research on the role of human pro-social motivation to maintain social order. I argue that social order can be conceptualized as a public good game. Past attempts to explain social order typically relied on the assumption of selfish and rational agents (“homo economicus”). The last twenty years of research in behavioural and experimental economics have challenged this view. After presenting the most important findings of recent research on human pro-sociality I discuss the evidence on three pillars of the maintenance of social order. The first pillar is internalized norms of cooperation, sustained by emotions such as guilt and shame. The second pillar is the behaviour of other people who typically are “conditional cooperators” willing to cooperate if others do so as well. This motivation can sustain cooperation if enough people cooperate but can jeopardise social order if many others follow selfish inclinations. The third pillar are sanctions meted out to anyone who does not cooperate; ideally punishment can work as a mere threat without being executed much. The chapter also presents some evidence on the cross-cultural variability of some findings, in particular with regard to punishment behaviour. The chapter concludes with remarks on future research.
Keywords: C90; 330; social order; social dilemma; pro-sociality; strong reciprocity; moral emotions; social norms; conditional cooperation; punishment; rule of law